9514 1404 393
Answer:
(x, y) = (2, -2)
Explanation:
We would normally choose to use substitution when x or y could be easily solved-for without having fractions involved. That is not the case here. However, we observe that the term 3y appears in both equations, so we can substitute for "3y" instead of "y".
From the second equation, ...
3y = 5x -16
Substituting into the first equation, ...
2x +(5x -16) = -2
7x = 14 . . . . . . . . . add 16
x = 2 . . . . . . . . . . divide by 7
Using our equation for y, we get ...
3y = 5(2) -16 = -6
y = -2 . . . . . . . . . divide by 3
The solution is (x, y) = (2, -2).